The Acoustic Response of Structures to Blast-Induced Ground Vibration: Fact or Fiction - W. J. Birch; G. D. Rangel-Sharp; R. Farnfield (International Society of Explosives Engineers, 2007)
It is widely recognised that complaints from members of the public relating to blasting operations are related to both ground vibration and air overpressure. It is also known that a complaint is more likely to be generated if the person is inside of a structure at the time of the blast. Reports relating to such complaints often refer to ‘noise’ inside the structure with terms like ‘rattling’ commonly being employed. Such acoustic response is widely perceived within the blasting industry to be directly related to high levels of air overpressure although there appears to have been very little research carried out specifically related to this effect.